2020
DOI: 10.1186/s11671-019-3241-2
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Nano-Structured Extended-Release Local Anesthetics

Abstract: Extended-release local anesthetics (LAs) have drawn increasing attention with their promising role in improving analgesia and reducing adverse events of LAs. Nano-structured carriers such as liposomes and polymersomes optimally meet the demands of/for extended-release, and have been utilized in drug delivery over decades and showed satisfactory results with extended-release. Based on mature technology of liposomes, EXPAREL, the first approved liposomal LA loaded with bupivacaine, has seen its success in an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 166 publications
0
28
0
Order By: Relevance
“…DepoFoam™ technology is also utilized to tackle pain management before and after surgical procedure. Exparel® (bupivacaine liposome), approved by FDA in 2011, is a longer acting form of traditional bupivacaine 105 . Day et al.…”
Section: Strategies To Manipulate the Drug Release From Delivery Systemsmentioning
confidence: 99%
“…DepoFoam™ technology is also utilized to tackle pain management before and after surgical procedure. Exparel® (bupivacaine liposome), approved by FDA in 2011, is a longer acting form of traditional bupivacaine 105 . Day et al.…”
Section: Strategies To Manipulate the Drug Release From Delivery Systemsmentioning
confidence: 99%
“…The component that was sensitive to the enzyme is the azo bond linked to the MSNs and chitosan. The results showed that the azo bond was broken in the presence of colon enzyme secreted by colonic microflora [ 179 ]. In another work, the same enzyme was used as a response to MSNs with guar gum as the pores’ cap.…”
Section: Msns As Smart Drug Delivery Agentmentioning
confidence: 99%
“…Exparel® was the first approved liposomal LA to combine racemic bupivacaine with liposomes. Polymersomes have advances over liposomes with complementary profiles, inspiring the emergence of hybrid carriers [35,36]. Also, multilamellar vesicles with ropivacaine are being investigated to prolong its analgesic effect [37].…”
Section: Amino Amide Lasmentioning
confidence: 99%